2010
DOI: 10.1002/cncr.25190
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor κB transcription factors are coexpressed and convey a poor outcome in ovarian cancer

Abstract: BACKGROUND: Recent work has suggested a role for nuclear factor jB (NF-jB) in the propagation of ovarian cancer cell lines, but the significance and mechanism of NF-jB in ovarian cancer is unknown. The authors hypothesized that the NF-jB pathway is over activated in aggressive ovarian cancers. METHODS: The levels of 3 NF-jB transcription factors, the activating inhibitors of NF-jB (IjB) kinases, and the NF-jB target matrix metalloproteinase 9 (MMP9) were assessed by immunohistochemistry in specimens of ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
116
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(125 citation statements)
references
References 28 publications
(55 reference statements)
5
116
1
3
Order By: Relevance
“…Uncontrolled activation of NF-kB signaling has been implicated in propagation of a large number of malignancies including ovarian cancer (1,2). Intrinsically or constitutively active NF-kB has been defined critical in the promotion of cell proliferation, angiogenesis, metastasis (3), and development of drug resistance (4) in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Uncontrolled activation of NF-kB signaling has been implicated in propagation of a large number of malignancies including ovarian cancer (1,2). Intrinsically or constitutively active NF-kB has been defined critical in the promotion of cell proliferation, angiogenesis, metastasis (3), and development of drug resistance (4) in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that an increase in cytoplasmic NFj-B transcription factor p50 was significantly associated with poorer patient survival, whereas no association was found between NFj-B transcription factor p65 and patient survival. 24 COX is a key regulatory enzyme in the prostaglandin/eicosanoid synthetic pathway. Two isoforms of COX have been identified, COX-1 and COX-2.…”
Section: Recently Kurman Et Al Proposed a New Classification Ofmentioning
confidence: 99%
“…Lin et al (2007) suggested an important role for NF-κB in the propagation of ovarian cancer cell lines. Annunziata et al (2010) found the NF-κB pathway is over-activated in aggressive ovarian cancers. In addition, a recent report by Fan et al (2011) suggested that a functional promoter polymorphism in NFKB1 gene increases the risk of advanced ovarian cancer in a population from northeast China.…”
Section: Introductionmentioning
confidence: 99%
“…Mammals carry 5 members of the NF-κB family including p50/p105, p65/RelA, c-Rel, RelB, and p52/p100. Although many dimeric forms of NF-κB have been detected, the major form of NF-κB is a heterodimer of the p50 and p65/RelA subunits, encoded by the NFKB1 and RELA genes, respectively (Lin et al, 2007;Annunziata et al, 2010). Recently, NF-κB signaling activation in ovarian cancer development and progression has been studied intensely (Chen et al, 2001;Karin, 2006;Maeda and Omata, 2008).…”
Section: Introductionmentioning
confidence: 99%